Financial Capability as a Predictor of Financial Satisfaction among Catholic Higher Education Employees: A Sequential Explanatory Mixed Method Inquiry - Nawanao, Mary Mae; Lopena, Grace (Technium Social Sciences Journal, 2024)
Understanding the financial capability and satisfaction of Catholic Higher Education Institution (CHEI) employees is crucial in addressing their financial well-being. Hence, this paper quantitatively assessed the financial capability and financial satisfaction of CHEI employees. Meanwhile, the qualitative phase explored the factors influencing financial capability and financial satisfaction through interviews. By employing a sequential explanatory mixed-method approach, the research provided a holistic understanding of how financial capability impacts financial satisfaction and explore potential strategies to enhance their financial well-being. The quantitative phase involved a self-made research instrument. The researcher employed tools like frequency distribution, mean, standard deviation, and regression analysis. For the qualitative phase, data collection involved a semi-structured interview. Lichtman’s 3 Cs analyzed the transcribed data. The quantitative results revealed that the CHEI employees has a high financial capability. However, they are financially dissatisfied. In their demographics, income, educational attainment, and employment classification has a significant relationship of CHEI financial capability. In financial satisfaction, only income and educational attainment has a significant relationship. Moreover, the qualitative results revealed that having alternative means of living, receiving spousal support, and having fewer dependents are key elements that enhance the financial resilience and flexibility of CHEI employees. However, despite their financial capability, the research indicates that CHEI employees may face financial dissatisfaction linked to employment-related issues. Factors such as limited career advancement opportunities and lower monthly salary levels are identified as significant contributors to their financial dissatisfaction.